Penggunaan Tanda Tangan Elektronik dalam Penyelenggaraan E-Government Guna Mewujudkan Pelayanan Publik yang Efisien - Annisa Noor El Izzah; Wasis Sugandha (Journal of Law, Society, and Islamic Civilization, 2021)
This study aims to discuss Electronic Signatures in the implementation of E-Government in order to realize efficient public services to find out how the system and the problems of using electronic signatures of public officials in the implementation of e-government. The method used in this research is a normative research method with a prescriptive nature. The approach in this research is the statutory and conceptual approach. The legal materials used in this study are primary legal materials consisting of legislation and secondary legal materials obtained through library materials. The data analysis technique uses deductive logic. The results of this study indicate that the application of e-government information technology in this case the use of electronic signatures will bring the government to be more efficient and effective in terms of public services as well as administrative processes and internal communications. There are two main legal problems in the use of electronic signatures by public officials, namely regarding the legal power of electronic signatures and the security of the electronic signature itself from forgery.Keywords : Electronic Signature, E-government, Public Service, Efficient